Debt Intolerance : Threshold Level and Composition - Matsuoka, Hideaki (World Bank, Washington, DC, 2020)
Fiscal vulnerabilities depend on both the level and composition of government debt. This study examines the role of debt thresholds and debt composition in driving the non-linear behavior of long-term interest rates through a novel approach, a panel smooth transition regression with a general logistic model. The main findings are threefold. First, the impact of the expected public debt level on interest rates rises exponentially when the share of foreign private holdings exceeds approximately 20 percent of government debt denominated in local currency. Second, when the share of foreign private investors is 30 percent, an increase in the share of foreign private holdings of government debt could raise long-term interest rates once the public debt-to-GDP ratio exceeds 60 percent of GDP, offsetting the downward pressure on long-term interest rates from higher market liquidity. Third, out-of-sample forecasts of this novel non-linear model are more accurate than those of previous methods.